The Duality of Community Development and Community Relations Functions CSR Program of Oil and Gas Company: Case Study of Oil and Gas Company in Subang, West Java - Yuliasari, Putri (UI Scholars Hub, 2020)
After the Reformation, various companies implement CSR programs with various goals, features, and forms. This article discusses the latent function of the BROERI Program of PT Pertamina EP Asset 3 Subang Field as an instrument to build corporate relations with its stakeholder (Community Relation), besides its manifest function in capacity building and community independence (Community Development). The previous studies have been more dominant in highlighting and focusing on the evaluation of community development functions of the CSR programs, rather than their community relation function. Whereas for oil and gas companies, the risk of conflict with communities and other local stakeholders tends to be high and needs to be mitigated with appropriate CSR programs. The author argues that behind the design that is explicitly directed to manifest functions (Community Development), the CSR programs also have a crucial latent function as a medium of communication and negotiation with community stakeholders (Community Relations). The result of this research with the qualitative method shows that the BROERI Program of PT Pertamina EP Asset 3 Subang Field is less able to establish and increase the capacity of the community. Besides, the program also does not function optimally as a